Analytical solution for mechanical behavior characterization of sandy dolomite tunneling - Di Sun; Di Sun; Di Sun; Di Sun; Zhigang Tao; Zhigang Tao; Hong Yang; Haoche Shui; Xiaotian Lei; Xiaotian Lei; Fengnian Wang; Fengnian Wang; et al. (Frontiers in Earth Science, 2024)
Tunneling in sandy dolomite strata often faces hazards such as collapse, water inrush, and water–sand inrush, seriously threatening the safety of tunnel construction. There are currently limited studies on the mechanical behaviors of sandy dolomite tunnels. In view of this, an analytical solution for tunneling in sandy dolomite strata is derived in this study, and then parametric analysis is performed to analyze the mechanical response of rock mass in sandy dolomite tunnels. The results demonstrate five tunnel sidewall stress scenarios according to the different lateral pressure coefficients (λ). Varying λ values impact stress distribution and tunnel stability, with extreme values posing risks of instability. Tunnel safety is greatly reduced when rock stress approaches the plastic limit. At different internal friction angles, cohesion, and initial rock stresses, radial stress decreases gradually as the radius increases. The stress values under different conditions tend to be similar, while the effects of internal friction angle, cohesion, and initial rock stress on stress in the elastic zone decrease with increasing distance from the center of the tunnel. Under different internal friction angles and cohesion, the plastic zone radius increases with increasing distance from the excavation surface, and a larger internal friction angle and cohesion lead to an increase in stress. The stress and cohesion of a rock mass significantly affect the plastic zone radius, and an increase in tunnel excavation radius also leads to an increase in the radius of plastic zone. These findings provide a reference and insight for similar geotechnical engineering practices in the future.